Instrumented Gait Analysis: A Tool in the Treatment of Spastic Gait Dysfunction. Issue 6 (7th June 2016) - Moon, Daniel; Esquenazi, Alberto
Abstract : Spasticity is a term commonly used to describe a collection of muscle overactivity patterns associated with the upper motor neuron syndrome including actual spasticity, clonus, dystonia, co-contraction, associated reactions, and flexor or extensor spasms. Gait dysfunction in the upper motor neuron syndrome can be due to a combination of paresis, impaired coordination and balance, and muscle overactivity and contracture. Treatment options include physiotherapy, assistive devices, orthotic devices, oral and intrathecal medications, intramuscular chemodenervation, neurolysis, and/or neuro-orthopaedic surgical procedures. The objective evaluation of walking and its underlying muscle activation patterns can be performed by the simultaneous collection of joint kinematics, kinetics, and dynamic electromyography (EMG) data that serve as an extension of the physical examination to better discern primary gait deviations from compensatory gait deviations as well as underlying muscle overactivity from contracture. Despite the science behind instrumented three-dimensional gait analysis, its specific contribution to clinical and surgical decision-making is not well utilized because of its associated cost, the incorrect view by some insurance companies of gait analysis being a research technique, the dearth of qualified clinical gait and motion analysis laboratories accessible to adult patients, and limited access to orthopaedic surgeons who have experience in the treatment of neurological disorders for this patient population.